WEB SERVICES: reusable components in the reuse-oriented development process - Leal Gomes, Yuri; Gibertoni, Daniela (Revista Interface Tecnológica, 2022)
The reuse of pre-existing software or components is an approach that can be used in the development process in order to increase trust, reduce risks and deadlines. In this context, web services are considered components with a high possibility of reusability, however, their implementation process must be reusability-oriented, thus enabling their inclusion in a reuse-oriented development process. Therefore, the present work aims to investigate through the literature review, the relationship between the development of reusable web services with the reuse-oriented development process. It was concluded that the web services development process can be conducted through service engineering. By establishing activities responsible for designing reusable services, more reusable components will be made available. Therefore, by offering a large number of reusable components, there is an incentive to use reuse-oriented development approaches.